A homemade control system for the Peruvian courts - Guerrero Barreto, Dante Ramón (2022)
This work proposes an alternative to supplement the efforts made by the Peruvian Judiciary to improve the efficiency of judicial proceedings using information technologies. To this effect, the problems of this State Branch identified by the different studies issued in the past few years are described, explaining what a control system consists of and including a real story that occurred in Peru that proves that the proposal is viable.